Structural performance of cold-formed steel with self-compacting concrete in a composite beam system - Muhammad Lawan, Mustapha (2015)
The use of composite systems comprising of concrete and hot-rolled steel (HRS) sections is well established as observed in current design codes. But, there is limited technical information available about the use of composite systems that incorporates the use of light gauge steel sections, despite the potentials of the system in residential and light industrial constructions. Therefore, this research work investigated the structural performance of cold-formed steel (CFS) section with Self-Compacting Concrete (SCC) as a composite beam system, by means of shear connection mechanism of bolted shear connectors. The study comprised two components; experimental and theoretical works. The experimental work consisted of two phases; push-out and full-scale experimental tests. The push-out specimens were of the same dimension (800 mm x 600 mm x 75 mm). In push-out test, strength capability and ductility of the proposed bolted shear connectors were determined. Bolted shear connectors of M16, M14 and M12 of grade 8.8 were installed on the flanges of I-beam section of CFS using single nut and washer above and beneath through bolt holes of 17 mm, 15 mm and 13 mm diameters at a designated longitudinal interval of 150 mm, 250 mm and 300 mm respectively, and spaced laterally at 75 mm. The specimens were cast with SCC of grade 40 N/ mm2. Shear connector size and longitudinal spacing were the varied parameters, and their influence on the ultimate load capacity was investigated. The results showed that the size and the longitudinal spacing of the shear connectors had significantly influenced the ultimate load capacity. Ductility of the shear connectors was determined to be acceptable as an average characteristic slip capacity above 6 mm as recommended by Eurocode 4 was achieved by all shear connectors. Close agreement was recorded between experimental and theoretical values based on Eurocode 4 equations. In full-scale test program, longitudinal spacing employed was 250 mm and 300 mm excluding 150 mm spacing due to overlapping of stress fields as established in push-out test that led to strength reduction. The full-scale specimens were of the same dimension (4500 mm x 1500 mm x 75 mm) and were tested using a four-point bending test. The results showed that the ultimate load and ultimate moment capacities were influenced by the studied parameters as established in push-out test. Results of comparison between experimental and theoretical values revealed good agreement. In conclusion, the CFS-SCC composite beam system can be employed in small and medium size buildings, and in light weight construction industry.